(untitled) (Agroindustria, Sociedad y Ambiente, 2013)
This research was conducted in order to develop a proposal for the incorporation of products generated by Destilerias Unidas S.A in a food ration for the production of buffalo milk in the Botucal Agroindustrial Complex. The research design focused on a feasible project, which required a diagnostic phase of necessity, a feasibility phase and a final phase where the specific proposal develops. To do this, the entire distillate was characterized, showing a variability in chemical composition, then totally mixed rations based on theoretical fresh fodder and / or preserved supplemented with complete distillation through a software (LINDO) were formulated for the herd of buffaloes for nutritional requirements in different physiological states. This also helped to optimize the use of resources available at relatively low costs, increasing milk productivity on 3.5% to 4.5% with the expected consumption of 4% of body weight in dry matter. With this, the research can constantly make adjustments in feeding the flock, in order to maintain optimal nutritional balance according to their physiological state and finally further studies to determine the costs and influence on milk productivity and adding silage / or other products preserved by the full distillate.